Association between Cognitive Impairment and Hippocampal Subfield Volumes in Multiple System Atrophy - Atsuhiko Sugiyama; Hajime Yokota; Shigeki Hirano; Jiaqi Wang; Shoichi Ito; Satoshi Kuwabara (Parkinson's Disease)
This study aimed to explore morphological changes of hippocampal subfields in patients with multiple system atrophy (MSA) with and without cognitive impairment using FreeSurfer-automated segmentation of hippocampal subfield techniques and their relationship with cognitive function. We enrolled 75 patients with MSA classified as cognitively impaired MSA (MSA-CI, n = 40) and cognitively preserved MSA (MSA-CP, n = 35), as well as 68 healthy controls. All participants underwent three-dimensional volume T1-weighted magnetic resonance imaging. The hippocampal subfield volume was measured using FreeSurfer version 7.2 and compared among groups. Regression analyses were performed between the hippocampal subfield volumes and cognitive variables. Compared with healthy controls, the volume of the right cornu ammonis (CA) 2/3 was significantly lower in the MSA-CI group (P=0.029) and that of the left fimbria was significantly higher in the MSA-CP group (P=0.046). Results of linear regression analysis showed that the right CA2/3 volume was significantly correlated with the Frontal Assessment Battery score in patients with MSA (adjusted R2 = 0.282, β = 0.227, and P=0.041). The hippocampal subfield volume decreased in patients with MSA-CI, even at the early disease stages. Specific structural changes in the hippocampus might be associated with cognitive deficits in MSA.